Nitrate Ion Sensing Properties of Peripheral 3,4,5-Trimethoxyphenoxy and Chlorine Substituted Metallo and Metal-free Phthalocyanines - ODABAŞ, ZAFER (SPRINGER, 2022)
The purpose of this study is to investigate the capability of novel peripheral metal-free and metallo (2H, Fe, Co, Zn) mono nuclear phthalocyanines coated quartz crystal microbalance (QCM) sensor for the detection of nitrate ions in water. Although the synthesis of phthalocyanines is usually difficult and expensive, the novel phthalocyanine complexes are planned to be used as nitrate ion detectors in water because their synthesis is easy and cheap. The starting compound and the phthalocyanines were characterized by elemental analyses, FT-IR, UV-vis H-1-NMR, C-13-NMR and MALDI-TOF mass spectral data. The effect of metals on spectroscopic properties and aggregation behaviours of these novel phthalocyanines were investigated in different solvents. From nitrate ion detection tests, it was observed that the 2(3),9(10),16(17),23(24)-tetrachloro-2(3),9(10),16(17),23(24)-tetrakis(3,4,5-trimethoxyphen-oxy)phthalocyaninatozinc(II) functionalized sensor exhibits a low detection limit of 0.08 mg/mL with a rapid response within 15-22 s, which is superior to most of the commonly used methods. Our study provides a new strategy for rapid, and sensitive, detection of nitrates, and is promising for real-time and in-situ water quality monitoring. In addition, the nitrate ion adsorption kinetics of these compounds was also modelled according to three different kinetic models, namely pseudo first order kinetic model, Elovich model and interparticle diffusion kinetic model. It was observed that the adsorption kinetics obeys to the first order model for low concentrations of nitrate ions, while the Elovich model is the most appropriate to model nitrate ions adsorption for high concentration of nitrate ions.
Keywords: Synthesis; Phthalocyanine; 3,4,5-Trimethoxyphenoxy; Nitrate ion sensing; QCM; Adsorption kinetics; REAL-TIME; NITRITE; SENSOR; WATER; METALLOPHTHALOCYANINE; ADSORPTION; ELECTRODE; BEHAVIOR; OXIDE; DYES